Distribution and conservation status of Grifola frondosa (Polyporales, Basidiomycota) in Ukraine - Shevchenko, M.V.; Heluta, V.P.; Hayova, V.P. (Український ботанічний журнал, 2019)
Grifola frondosa is a nationally red-listed species in Ukraine. In the third edition of the Red Data Book of Ukraine
it is assigned to a category Vulnerable (VU). Previously, the fungus was known from 17 localities in nine regions of Ukraine:
Cherkasy, Dnipropetrovsk, Donetsk, Kharkiv, Kherson, Kyiv, Sumy, Ternopil, Transcarpatian, and the Autonomous Republic
of Crimea. Over the recent decade, G. frondosa has been also recorded in the following eight regions: Chernihiv, Chernivtsi,
Ivano-Frankivsk, Khmelnytskyi, Lviv, Rivne, Volyn, Zhytomyr, and Kyiv city. Thus, a number of known up to now localities
of G. frondosa increased from 17 to more than 40. However, the expanded number of records is due to additional data recently
provided from field observations by amateur mycologists, rather than a result of the increasing population trend of the fungus.
Based on the current distribution pattern of G. frondosa in Ukraine, its contemporary conservation status on the national level
was evaluated using the IUCN categories and criteria. The species was assessed as Endangered, EN under criteria 2 ( ).
This is the higher threat category as compared to Vulnerable (VU) in the current edition of the Red Data Book of Ukraine. For
conservation purposes, it is necessary to protect the already known sites, to search for new localities of the fungus, and to explore
possibilities of its re-introduction into natural habitats. Global distribution and the Red List status of G. frondosa in Europe are
briefly discussed. A list of currently known localities of the species in Ukraine and a distribution map of the reported sites are
provided. Grifola frondosa в Україні підлягає охороні на національному рівні. У третьому виданні "Червоної книги
України" вид віднесений до категорії "уразливий" (VU). Раніше гриб був відомий з 17 локалітетів у дев'яти областях
України – Дніпропетровській, Донецькій, Київській, Закарпатській, Сумській, Тернопільській, Харківській,
Херсонській і Черкаській, а також в Автономній Республіці Крим. Упродовж останнього десятиліття G. frondosa була
зареєстрована ще у восьми областях – Волинській, Житомирській, Івано-Франківській, Львівській, Рівненській,
Чернівецькій, Чернігівській і Хмельницькій та в місті Києві. Таким чином, кількість відомих локалітетів виду зросла
з 17 до понад 40. Однак це збільшення пов'язане насамперед з широким залученням до пошуків G. frondosa мікологіваматорів, а не є наслідком тенденції до збільшення чисельності гриба. На основі уточнених даних про поширення
G. frondosa в Україні проведено оцінку природоохоронного статусу цього виду на національному рівні з використанням
категорій і критеріїв МСОП. Вид оцінено як "зникаючий", EN за критеріями С2а(і). Ця категорія відповідає вищому
ступеню загрози порівняно із категорією "уразливий" (VU) у третьому виданні "Червоної книги України". Надалі
для збереження виду потрібно охороняти відомі його локалітети, проводити пошук нових місцезростань гриба та
досліджувати можливість його реінтродукції до природних місць існування. У статті стисло обговорюються загальне
поширення і природоохоронний статус G. frondosa в Європі. Наведено список відомих на сьогодні локалітетів та карта
поширення цього виду в Україні.